2014
DOI: 10.1007/s11368-014-1042-x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of three selected endocrine disrupting chemicals by aquatic colloids and sediments in single and binary systems

Abstract: Purpose Aquatic colloids are ubiquitous in natural river water, but their effects on the adsorption of pollutants by sediments are not fully understood. This study investigated the adsorption of three endocrine disrupting chemicals (EDCs) by aquatic colloids and sediments in single and binary systems. The role of aquatic colloids in the adsorption of EDCs by sediments in the binary system was evaluated. Materials and methods Water and sediment samples were collected from Huanyuankou (HS) and Lijin (LS) station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Thus, in this study we used environmentally relevant levels of BPA ranging from 10 to 1000 μg·kg −1 and TiO 2 -NPs concentrations from 1 to 100 mg·kg −1 for the treatments as shown in Table 1 . Uncertain parameters in biosolids have been reported, such as organic matter ( Simonin et al, 2021 ; Wu et al, 2017 ; Zhu et al, 2012 ) and soil colloid ( Campos et al, 2020 ; Philippe et al, 2018 ; Sun and Zhou, 2015 ). In order to avoid the discrepancy, agar media were used for the treatment and control groups and supplemented with growth medium ( Weigel and Glazebrook, 2002 ) (400 mL 1 × MS medium with 0.6% (g/g) agar powder).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in this study we used environmentally relevant levels of BPA ranging from 10 to 1000 μg·kg −1 and TiO 2 -NPs concentrations from 1 to 100 mg·kg −1 for the treatments as shown in Table 1 . Uncertain parameters in biosolids have been reported, such as organic matter ( Simonin et al, 2021 ; Wu et al, 2017 ; Zhu et al, 2012 ) and soil colloid ( Campos et al, 2020 ; Philippe et al, 2018 ; Sun and Zhou, 2015 ). In order to avoid the discrepancy, agar media were used for the treatment and control groups and supplemented with growth medium ( Weigel and Glazebrook, 2002 ) (400 mL 1 × MS medium with 0.6% (g/g) agar powder).…”
Section: Resultsmentioning
confidence: 99%
“…Distinctly, single layer adsorbate occurs in chemisorption, and the mechanism is influenced by the aforementioned treatment factors [163]. Adsorption technique for the removal of EDCs from various water sources using AC has received extensive efforts, which have yielded considerable progress in the last two decades [164][165][166]. For example, Temmink et al [139] and Kovalova et al [25] in their separate studies reported excellent EDCs removal using PAC, ranging between 84% and 99% under different operating adsorption conditions.…”
Section: Removal Of Endocrine-disrupting Compounds Via Adsorption Processmentioning
confidence: 99%
“…In natural aquatic systems, most pollutants are adsorbed to fine particles (Sun and Zhou, 2014). The sediments were dried under air at room temperature, homogenized, and passed through a 63 µm nylon sieve.…”
Section: Sediment Sampling and Characterizationmentioning
confidence: 99%
“…The sediments were dried under air at room temperature, homogenized, and passed through a 63 µm nylon sieve. The fraction containing particles with a size < 63 µm was sealed in plastic bags in the dark and stored at room temperature; only this fraction of sediments is considered to be geochemically important and evenly distributed in river cross-sections (Horowitz et al, 1990;Sun and Zhou, 2014). Thus, the sediment fraction with a size of < 63 µm is utilized in this experiment.…”
Section: Sediment Sampling and Characterizationmentioning
confidence: 99%